2018
DOI: 10.1111/1748-8583.12221
|View full text |Cite
|
Sign up to set email alerts
|

Incentives to move up: Effects of pay gaps between levels on employee performance

Abstract: Employees of a certain rank are motivated by the pay gap between them and the levels above (upward comparison), and the pay gap between them and the levels below (downward comparison). In some cases, employees face multiple upward comparisons such as immediate and subsequent upward comparisons. We hypothesise that upward comparison matters more than downward comparison, and in the case of multiple upward comparisons, the immediate one matters more than the subsequent ones. We also hypothesise that the pay gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Although the compensation gap between executives and employees has attracted considerable attention, our knowledge of its possible consequences from a corporate economic performance perspective is still rather limited and elusive [38]. On the one hand, Lazear and Rosen [39] proposed tournament theory, and indicated that an enterprise can establish a hierarchy to motivate employees.…”
Section: Compensation Gapmentioning
confidence: 99%
“…Although the compensation gap between executives and employees has attracted considerable attention, our knowledge of its possible consequences from a corporate economic performance perspective is still rather limited and elusive [38]. On the one hand, Lazear and Rosen [39] proposed tournament theory, and indicated that an enterprise can establish a hierarchy to motivate employees.…”
Section: Compensation Gapmentioning
confidence: 99%
“…Employee performance (EP): Employee performance is the product of employee-centric practices (Kooji et al, 2013) aimed at improving employee skillset and satisfaction TQM 33,6 (Guest, 2011). It is fostered by employee participation (Ogbonnaya and Messersmith, 2018), and commensurate wage package to performance (Chi et al, 2019). It is the exhibition of behaviours that align with firm goals and objectives (Lepak et al, 2006).…”
Section: Impact Of Quality Managementmentioning
confidence: 99%
“…The enthusiasm of employees not only depends on the level of their own pay, but also is affected by the management pay. Higher pay gap can induce low-level employees to make efforts to win competition prizes, rather than immerse themselves in past achievements [7,9]. In the case of a large number of competitors and increasing environmental uncertainty, in order to stimulate competition participants to improve their efforts and willingness to take risks, enterprises should increase the pay gap.…”
Section: Strategy and Pay Gapmentioning
confidence: 99%